126 CENTRAL ADIPOSITY IS ASSOCIATED WITH INCREASED PREVALENCE OF VERTEBRAL FRACTURES. (25th October 2022) - Feely, O; Laird, E; Hoey, L; Hughes, C; McNulty, H; Ward, M; Strain, JJ; Tracey, F; Molloy, A; Cunningham, C; Fallon, N; Lannon, R; et al.
Abstract: Background: Increased body weight and obesity are associated with greater bone mineral density (BMD) though effects on fracture risk appear to be site specific. In particular, the relationship between Body Mass Index (BMI), abdominal weight and Vertebral Fractures (VF) is complex. Some studies have found greater incidence of VF's with obesity though results are inconsistent. Recent evidence supports a stronger association between measures of abdominal fat and VF's. We aimed to examine the association between central adiposity and VF's in older Irish adults. Methods: Participants were from a large cross-sectional study of older Irish adults (aged >60) attending GP or hospital outpatient services. VF diagnosis was based on self-report (ie. clinical vertebral fracture) so we excluded those with a Mini Mental State Examination (MMSE) < 25. BMD was measured with DXA and patients taking antiresorptive or anabolic therapies were excluded. The relationship of waist hip ratio (a surrogate marker of central adiposity) with VF's was explored in regression models. Results: 2055 identified, mean age 69.8 ± 6.3 years (range 60-99), 58.6% female. Vertebral fracture prevalence was 6.3% (n=130). Waist hip ratio was positively associated with presence of a vertebral fracture after adjusting for age, sex, BMI, timed up and go, smoking, serum vitamin D, lumbar spine BMD and steroid use > 3 months (beta: 0.04,  P<0.001). Conclusion: We identified that central adiposity (as measured by waist/hip ratio) was associated with VF presence independent of several factors including BMI and spine BMD. This suggests that body fat distribution and/or altered bone quality may play a role. Visceral body fat (which is correlated with waist hip ratio) is associated with increased production of adipocytokines, altered vertebral geometry and micro-architecture, increased vertebral bone marrow fat and greater loading forces on the spine, all of which may mediate increased VF risk.